Peningkatan Kinerja Water Flow-Cooling pada Chiller Thermo 5000 untuk Pengukuran yang Lebih Baik pada XRD FMIPA UNS - David Harjanto; Arifin Musthafa (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
This work was created with the aim of developing maintenance techniques for equipment, namely the X-Ray Diffractometer (XRD) brand/model D8 Advance Made by Bruker Germany, especially in the Water Flow/Cooling Water unit in the Integrated Laboratory of the Faculty of Mathematics and Natural Sciences, Sebelas Maret State University, Surakarta, which has not been available so far. The X-Ray Diffractometer (XRD) tool is currently widely used by students and researchers in understanding and studying the crystal structure of a material. To prevent water flow problems, it is very important to maintain and check the water cooling system regularly to ensure continued peak performance. As part of the filter cooling system in the Water Flow/Cooling Water chiller, it has a role in filtering particles that enter the hose that flows through the X-Ray tube to prevent overheating. The water flow sensor monitors the water flow in the X-Ray Diffractometer (XRD) cooling system, playing an important role in the redundant safety system of the XRD unit and supporting the accuracy and reliability of consistent XRD data. The XRD system is programmed to alert the operator and shut down the X-ray generator if the water flow rate drops below a safe threshold—below approximately 3.6 liters per minute (some machines have a two-stage shutdown process/some go into standby mode). Over time, the filter becomes contaminated with debris, which restricts the water flow to the X-ray Tube, resulting in inaccurate readings from the water flow sensor, which can lead to overheating and potential damage to the X-ray tube. The X-ray Diffractometer (XRD) cannot operate without the support of the Water Flow/Cooling Water system unit on the X-ray tube detector and X-ray generator. Therefore, a regular maintenance system is required by replacing several filters and replacing the water in the Flow/Cooling Water to ensure the equipment operates properly and the X-ray Generator has an optimal.